Sifat Fisika Kimia dan Organoleptik Cookies Beras Hitam (Oryza sativa L. indica) - Sih Pratiwi, Eko Kanti (Universitas Dr Soetomo, 2018)
Black rice (Oryza sativa L.indica) is a dark black rice and useful as a super food good for health, because of its high fiber content. Utilization of black rice as a d product is still very minimal. The objective of this research is to know the physical and chemical properties of cookies with fortification of black rice flour. This research method used non factorial RAL (non factorial design) with five level: control (F0), fortification of black rice flour (F1, F2, F3 and F4 = 2,5%, 5%, 7,5% and 10 %). The results of physical analysis of color and brightness indicate that the the percentage of fortification of black rice flour, the brightness decreases, while the texture (hardness) is higher. The result of chemical consisting of water, ash, fat, protein and fiber content, in e with SNI quality of cookies, while for sensory (organoleptic) color test is getting brown (F4), harder texture (F4) with flavors acceptable to panelists rather sweet, somewhat savory typical cookies